GDF-15 as a Therapeutic Target of Diabetic Complications Increases the Risk of Gallstone Disease: Mendelian Randomization and Polygenic Risk Score Analysis - Yu, Lili; Zhou, Yajing; Wang, Lijuan; Zhou, Xuan; Sun, Jing; Xiao, Jiarui; Xu, Xiaolin; Larsson, Susanna C.; Yuan, Shuai; Li, Xue (Frontiers in Genetics, 2022)
Growth differentiation factor 15 (GDF-15) levels have been revealed as a robust biomarker for metformin use. We conducted Mendelian randomization (MR) analysis to explore association between GDF-15 and gallstone disease to inform potential therapeutic effects targeting on GDF-15. Four genetic variants associated with GDF-15 levels at p<5×10-8 were selected as instrumental variables from a genome-wide association meta-analysis including 21,758 individuals. Two-sample MR analysis was conducted using summary-level data from UK Biobank (10,520 gallstone cases and 350,674 controls) and FinnGen consortium (19,023 gallstone cases and 195,144 controls). Polygenic risk score analysis using individual-level data in UK biobank was performed to complement the MR findings by examining the non-linearity of the association. Diabetic complications were taken as positive controls to validate the therapeutic effect targeting on GDF-15. Linear and non-linear associations between genetically predicted GDF-15 levels and gallstones were estimated with stratification by diabetic status. In two-sample MR analysis, the odds ratio (OR) of gallstones was 1.09 (95% confidence interval (CI), 1.03-1.15; p=0.001) for one standard deviation increase in genetically predicted GDF-15 levels in the meta-analysis of two datasets. Polygenic risk score analysis found this association to be U-shaped (p=0.037). The observed association was predominantly seen in non-diabetic population (OR=1.11, 95% CI: 1.01-1.21; p=0.003). An inverse association between genetically predicted GDF-15 levels and diabetic complications (OR=0.77, 95% CI: 0.62-0.96; p=0.023) was observed, validating the potential therapeutic effects targeting on GDF-15 levels. This MR study indicates that increased risk of gallstone disease should be taken into account when considering GDF-15 as a therapeutic target for diabetic complications.